Hypomagnesemia in Diabetic Patients and Its Correlation with Glycemic Control: Hypomagnesemia and Glycemic Control - Pervaiz, Abida; Salman, Sadia; Wali, Muhammad Zishan Akhter; Pasha, Usman; Baig, Amena Moazzam; Jamil, Muhammad Zahid; Ullah, Ismat (Pakistan Journal of Health Sciences, 2025)
Diabetes mellitus is a growing pandemic of the modern era with a wide array of complications. Better glycemic control is linked to improved survival and quality of life in diabetes patients. Serum magnesium levels have been postulated to adversely affect glycemic targets. Objectives: To determine hypomagnesemia prevalence in diabetic patients and its correlation with glycemic control. Methods: This cross-sectional observational study was conducted over six months from January 2025 to June 2025 at the diabetic clinical Jinnah Hospital, Lahore. A total of 174 patients fulfilling the inclusion criteria were enrolled in the study following a non-probability consecutive sampling technique. Informed consent was obtained from the participant. Data were recorded on a predesigned proforma, and analysis was run using SPSS version 25.0 version. Results: Out of the total 174 patients, 51 patients had normal magnesium levels, and 123 patients were hypomagnesemic. Poor glycemic control (HbA1C>7.0%) was significantly more prevalent (p=0.001) in hypomagnesemic patients. Although most of the female patients were having low serum magnesium levels (n=77), this gender difference was non-significant (p-value=0.450). Age-wise distribution of hypomagnesemia showed significantly more predilection (p=0.001) for 45 to 60 years age patients. Conclusions: The study concluded that hypomagnesemia is significantly linked to poor glycemic control in diabetic patients. Further studies are needed to explore the relationship between serum magnesium and dysglycemia.